PERANAN PENYIDIK PEGAWAI NEGERI SIPIL DINAS TANAMAN PANGAN HORTIKULTURA DAN PERKEBUNAN PROVINSI RIAU DALAM MENANGANI PENYEBARAN BENIH SAWIT PALSU BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1992 TENTANG SISTEM BUDIDAYA TANAMAN - Damanik, Martin Ade Insani; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The practice of circulating fake oil palm seedlings is an act that is against the law which can be punishable by punishment as regulated in Law Number 12 of 1992 concerning Plant Cultivation Systems, namely Article 60 paragraph (1) letters b and i. The number of criminal acts in the circulation of fake oil palm seeds in Riau Province has disturbed various groups, especially farmers. The role of the Plantation Civil Servant Investigator (hereinafter abbreviated as PPNS Perkebunan) then began to be questioned as the Investigator who has the task of investigating criminal acts in the plantation sector, one of which is to investigate the criminal act of spreading fake oil palm seeds.This type of research can be classified into the type of sociological research. The research location is the Department of Food Crops, Hulticulture and Plantation Riau Province. The data sources used are primary data and secondary data. Data collection techniques are interviews, questionnaires and literature review using deductive methods, namely drawing conclusions from general matters to specific matters.From the results of the research, there are three main things that can be concluded, First, the role of civil servant investigators of the Riau Province Plantation Service in tackling the spread of fake oilseeds is as an official who is authorized by Law No. 12 of 1992 on Plant Cultivation Systems to carry out investigations. Against the criminal case of spreading fake oil palm seeds that occurred in the Riau Province. Second, Obstacles to Civil Servant Investigators in overcoming crimes in the field of crop cultivation, especially the crime of spreading fake oilseeds,including weak coordination between law enforcers, main actors who are difficult to penetrate the law, inadequate facilities and infrastructure, and limited budget funds. Third, Law enforcement efforts carried out by Civil Servant Investigators in preventing the spread of fake oil palm seeds, such as providing appeals to the community, especially oil palm farmers, increasing supervision in the circulation of oil palm seeds and providing legal counseling.Keywords: Role of - Plantation PPNS - Investigation - Fake Oil Palm Seeds